A New Upper Bound on the Infinity Norm of the Inverse of Nekrasov Matrices - Lei Gao; Chaoqian Li; Yaotang Li (Journal of Applied Mathematics)
A new upper bound which involves a parameter for the infinity norm of the inverse of Nekrasov matrices is given. And we determine the optimal value of the parameter such that the bound improves the results of Kolotilina, 2013. Numerical examples are given to illustrate the corresponding results.